Metabolic Fingerprinting for Identifying the Mode of Action of the Fungicide SYP-14288 on Rhizoctonia solani - Liang, Li; Cheng, Xingkai; Dai, Tan; Wang, Zhiwen; Li, Jin; Li, Xueming; Lei, Bin; Liu, Pengfei; Hao, Jianjun; Liu, Xili (Frontiers in Microbiology, 2020)
The fungicide SYP-14288 has a high efficiency, low toxicity, and broad spectrum in inhibiting both fungi and oomycetes, but its mode of action (MoA) remains unclear on inhibiting fungi. In this study, the MoA was determined by analyzing the metabolism and respiratory activities of Rhizoctonia solani treated by SYP-14288. Wild-type strains and SYP-14288-resistant mutants of R. solani were incubated on potato dextrose agar amended with either SYP-14288 or one of select fungicides acting on fungal respiration, including complex I, II, and III inhibitors; uncouplers; and ATP synthase inhibitors. Mycelial growth was measured under fungicides treatments. ATP content was determined using an ATP assay kit, membrane potential of mitochondria was detected with the JC-1 kit, and respiratory rate was calculated based on the measurement of oxygen consumption of R. solani. A model of metabolic fingerprinting cluster was established to separate oxidation inhibitors and phosphorylation inhibitors. All the results together displayed a clear discrimination between oxidation inhibitors and phosphorylation inhibitors, and the latter inhibited ATP synthase production having or uncoupling activities. Based on the model, SYP-14288 was placed in phosphorylation inhibitor group, because it significantly reduced ATP content and membrane potential of mitochondria while increasing respiratory rate in R. solani. Therefore, the MoA of SYP-14288 on R. solani was confirmed to involve phosphorylation inhibition and possibly uncoupling activity.